Sistemas dopaminérgicos e ação antipsicótica: abordagens experimentais e teóricas - Tort, Adriano Bretanha Lopes (2005)
The aims of this work were the search for new atypical antipsychotics presenting low cost and the understanding of the mechanism of action leading to atypical antipsychotic profile. The results obtained are presented in two distinct parts based on their nature, namely, experimental (first part) or theoretical (second part). For the development of the first part, a webcam based software to measure locomotion of rodents was programmed. After that, it was investigated the effect of guanosine, flunarizine and cinnarizine on animal models of psychosis, as well as in other behavioral tasks. Guanosine was chosen because it has been shown to interact with the glutamatergic system – which is known to be involved in the pathophysiology of schizophrenia – by promoting astrocytic glutamate reuptake. Flunarizine and cinnarizine, two calcium channel blockers commonly used in many countries to treat vertigo and migraine, were chosen because they were shown to induce extrapyramidal signs in elder patients, which was later related to moderate antagonist properties at dopamine D2 receptors. Guanosine was able to reduce a NMDA antagonist (MK-801) induced hyperlocomotion, whereas it had no effect on the hyperlocomotion induced by amphetamine, and it is discussed that its utility as antipsychotic drug should be further evaluated. Both cinnarizine and flunarizine were able to reduce the hyperlocomotion induced by MK-801 and amphetamine at doses that presented no significant cataleptic behavior. It was therefore concluded that these compounds have a potential atypical antipsychotic profile, with the advantage of already approved for commercial use, presenting well tolerability and very low cost when compared to current commercially available atypical antipsychotics. The second part of this thesis presents some theoretical mathematical results that can be derived from the law of mass action theory applied to receptor binding linked with known PET experimental data. These results present insights to the understanding of the differences between typical and atypical profile of antipsychotics regarding the generation of extrapyramidal syndrome. It is argued that cultural and commercial aspects related to the nowadays employed posology of typical antipsychotics can be responsible for the difference seen in profile, once some typical antipsychotics are prescribed in proportionally higher doses in relation to their affinities, leading therefore to higher dopaminergic blockade. A short plasmatic half-life is also pointed as a possible important factor leading to an atipical profile. Moreover, the second part of this thesis also points to some misconception currently being used in the scientific literature regarding the time-course of dopaminergic occupation, such as the concept of receptor occupation half-life. As a last theoretical based result, it is proposed an algorithm for antipsychotic dose reduction in patients presenting extrapyramidal signs and symptoms.